Software Component Reusability Classification in Functional Paradigm - Manjhi, Devesh; Chaturvedi, Amrita (2019 IEEE International Conference on Electrical, Computer and Communication Technologies (ICECCT), 2019)
Reusing the software components can save time, money and resources, and upgrade the quality of the software being developed. Functional paradigm seems to be a platform that can support code reuse better than object-oriented or procedural programming paradigms. This work focuses on identifying potentially reusable components in functional programming paradigm. To conduct the experiments, various software metrics of software components written in Haskell have been used. In this research work, the Self-Organizing Map algorithm is used to cluster the functions from three Haskell packages into three different classes of reusability. Clustering of functions is based on metrics threshold and their average values.